KAJIAN HUBUNGAN KEBIJAKAN BAURANPEMASARANDAN VOLUME PENJUALAN GULA MERAH (SAKA) RAKYAT DI KABUPATEN TANAH DATAR SUMATERA BARAT - Sari, Rina; Nofialdi, Nofialdi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Brown sugar (saka) is one of alternative goods to fill sugar demand in Indonesia. This product is mainly produced by local agroindustries that disperse in many regions, one of the location is in Tanah Datar Regency. The aims of this study are to describe the marketing mix and to analyze the relation between marketing mix and selling volume of brown sugar in Tanah Datar Regency. Variables of this research are 4P of marketing mix and selling volume. The data is collected from farmer who produced traditionally, that spread in three district, then using quantitative analyze. The result of this research shows that product is molded by piece of coconut shell (diameter: 3-5 cm), the color is brown, reddish and yellowish, the selling price about Rp 10.000 - 15.000/Kg, and distributted through collecting traders or directly sold in market, and also have no promotion yet. The result of Chi Square analyze shows that there are relation between selling price variable with product variable, whereas place/ distribution variable is not.